Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai pada PT. BPR Sentral Arta Asia Kota Lumajang - Mohammad Fathoni; Elis Anita Farida (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
This study aims to analyze the influence of work motivation on the performance of employees at PT BPR Sentral Arta Asia (SAA) in Lumajang City, East Java. In the context of an increasingly competitive banking industry, companies require human resources who are not only competent but also possess strong internal and external drive to achieve organizational goals. This research employed a quantitative approach with a sample of 45 employees selected randomly. Data were collected through observation and questionnaires, then analyzed using validity tests, reliability tests, and simple linear regression. The findings reveal that work motivation has a significant positive effect on employee performance. This demonstrates that enhancing both intrinsic and extrinsic motivation can improve productivity and service quality, thereby supporting the company's long-term objectives. The determination coefficient (R²) of 45.2% indicates that motivation contributes significantly to performance, while the remaining 54.8% is influenced by other factors not examined in this study.